Outsourcing library operations in academic libraries : an overview of issues and outcomes/with a foreword by Katina Strauch. Englewood, Colo.: Libraries Unlimited, 1998. xix, 215 p. - Romanos de Tiratel, Susana (2001)
Fil: Romanos de Tiratel, Susana. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Investigaciones Bibliotecológicas; Argentina.